The Implementation of Bahasa Inggris Pemula In Enhancing Students’ Vocabulary Mastery Improving - Mira Mail; Husnani Aliah; Puspa Sari (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study was to determine the increase in vocabulary of class XI students through the implementation of bahasa inggris pemula applications at SMK Negeri 4 Palopo City, with a quantitative approach and a single group pretest posttest type of research. The data analysis technique used in this study is the t test. The results showed that the significance value of the t-test was less than 0.05, namely 0.000, and the t-count results were greater than t-table, namely t-count with a value of 5.080, which was greater than the t-table value of 2.093. Thus it was concluded that there was an effect of using Bahasa Inggris Pemula applications on the level of students' English vocabulary mastery.